Analisis rasio keuangan pada perusahaan sub sektor kimia yang terdaftar di Bursa Efek Indonesia - Mustafa, Yusufi Arif; Apandi, Aden (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
This study aims to analyze the financial performance of chemical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period by using four key financial ratios: liquidity, solvency, activity, and profitability. The research employed a quantitative approach using time series trend analysis and comparative analysis among companies. The results indicate that, in general, chemical sub-sector companies maintain adequate liquidity levels, demonstrating their ability to meet short-term obligations. In terms of solvency, most companies are able to keep their debt proportions within a reasonable range, although several firms still rely heavily on external financing. For the activity ratio, companies such as PT Indo Acidatama, PT Unggul Indah Cahaya, and PT Budi Starch & Sweetener exhibit high efficiency in utilizing assets to generate sales. However, the profitability ratio (ROA) reveals that most companies operate below the 5% threshold, indicating suboptimal profit efficiency. Overall, the financial performance of the chemical sub-sector remains stable but not yet optimal, highlighting the need for improved operational efficiency, debt management, and asset utilization strategies to enhance competitiveness in the future.